Nanomedicine applied to cardiovascular diseases: Latest developments - Martín Giménez, Virna Margarita (2017)
Cardiovascular diseases are a major cause of disability and they are currently responsible for a significant number of deaths in a large percentage of the world population. A large number of therapeutic options have been developed for the management of cardiovascular diseases. However, they are insufficient to stop or significantly reduce the progression of these diseases, and may produce unpleasant side effects. In this situation, the need arises to continue exploring new technologies and strategies in order to overcome the disadvantages and limitations of conventional therapeutic options. Thus, treatment of cardiovascular diseases has become one of the major focuses of scientific and technological development in recent times. More specifically, there have been important advances in the area of nanotechnology and the controlled release of drugs, destined to circumvent many limitations of conventional therapies for the treatment of diseases such as hyperlipidemia, hypertension, myocardial infarction, stroke and thrombosis.